(untitled) (Palíndromo, 2014)
The essay attempts to discuss the works of Marcel Duchamp in the first half of twenty century, examining his rebels proposal in the political-institutional en- vironment of his time and a specific ques- tion: the relation between Art and Concept in this production, attempting to the ways in which ones de redefinition of the artis- tic space and the artistic object conduces to propose a new notion of Art and a new notion of Artist. Such redefinition shows a significant politic value, since it situates the artist as a rebel able to question the exis- ting order and an institutional discourse that seeks to frame the art object within predictable limits.